Research is not a 'scary' word: Registered nurses and the barriers to research utilisation. (March 2017) - Hendricks, Joyce; Cope, Vicki
The aim of this study was to find out whether registered nurses read research articles, understand them and translate the research to practice. There is a problem with research knowledge translation in the clinical setting. Despite exposure to research, registered nurses often distance themselves from reading nursing research. A point-prevalence survey was conducted on a sample of registered nurses in a peripheral hospital in Western Australia. The survey was distributed to all wards of the hospital ( n = 7). One-hundred and five ( n = 105) registered nurses were eligible to participate. Ninety-five ( n = 95) completed and the survey. The survey consisted of 11 general questions and an open-ended question. The majority of registered nurses in clinical practice found research articles difficult to understand because of research jargon. Most indicated that they sometimes or never understood what they are reading. Almost all nurses revealed that if research articles were in a 'simpler' language they would read them more and apply what they had learned. Promoting a common, user-friendly language in a research abstract or summary which is targeted to the registered nurse audience may assist in finding a common knowledge exchange between researchers and nurses and so help bridge the gap between research and practice.